1999
DOI: 10.1046/j.1432-1327.1999.00679.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspartyl proteases in Caenorhabditis elegans

Abstract: Crude homogenates of the nematode Caenorhabditis elegans exhibit maximal proteolytic activity under acidic pH conditions. About 90% of this activity is inhibited by the oligopeptide pepstatin, which specifically inhibits the activity of aspartyl proteases such as pepsin, cathepsins D and E or renin.We have purified enzymes responsible for this proteolytic activity by a single-step affinity chromatography on pepstatin±agarose. Analysis of the purified fraction by 1D SDS gel electrophoresis revealed six bands ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 19 publications
(24 reference statements)
0
25
0
Order By: Relevance
“…Several aspartic proteases have also been described in different parasitic nematodes, including hookworms (Williamson et al 2004), S. stercoralis (Gallego et al 1998), Haemonchus contortus (Longbottom et al 1997) and Onchocerca volvulus (Jolodar et al 2004) and in the free-living nematode Caenorhabditis elegans (Geier et al 1999). In the hookworms, these proteases play an important role in haemoglobin digestion in the intestine and in tissue degradation during the larvae migration in the mammalian host (Williamson et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Several aspartic proteases have also been described in different parasitic nematodes, including hookworms (Williamson et al 2004), S. stercoralis (Gallego et al 1998), Haemonchus contortus (Longbottom et al 1997) and Onchocerca volvulus (Jolodar et al 2004) and in the free-living nematode Caenorhabditis elegans (Geier et al 1999). In the hookworms, these proteases play an important role in haemoglobin digestion in the intestine and in tissue degradation during the larvae migration in the mammalian host (Williamson et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, our pH assessment with different acid-base indicators (unpublished data) suggested that the pH value is ϳ5.0 in the intestine of the nematode C. elegans. The pH optimum for most protease activity in intestinal crude extracts from C. elegans was found to be ϳ5 (17,42), implying the possibility of a mildly acidic pH in the intestinal lumen (31).…”
Section: Discussionmentioning
confidence: 99%
“…microplus (Cruz et al, 2010), 60 kDa and 30 kDa from Trichomonas vaginalis (Sommer et al; and 35 to 52 from Caenorhabditis elegans (Geier et al;.…”
Section: Parasite Proteins Isolated By Serine-protease Inhibitors Affmentioning
confidence: 99%